Wireless Sensor Node with Passive RFID for Indoor Monitoring System - Norsaidah Muhamad Nadzir; M.K.A. Rahim; F. Zubir; A. Zabri; H.A. Majid (Institute of Advanced Engineering and Science, 2017)
This paper discusses the development of an indoor monitoring system based on passive radio frequency identification (RFID) system and Raspberry Pi 3. There are two algorithms designed for this project where the first is to link the RFID module to the Raspberry Pi 3, and the other one is to send the data obtained to a database over wireless network via UDOO Quad as a secondary router. The result is then displayed on a localhost generated using XAMPP. The objective of this project is to realize a monitoring system that incorporates different systems such as Raspberry Pi 3, UDOO Quad, and also RFID module by designing algorithms using Python and C programming language. Plus, the performance of the system is also analyzed using different type of antennas such as the Raspberry Pi 3 Antenna, monopole antenna, and a Yagi Uda antenna in terms of power received versus distance in both line of sight position and non-line of sight position. Finally, antenna that produces the best performance for line-of-sight (LOS) propagation is Yagi Uda antenna while monopole antenna is better when it comes to non-line-of-sight (NLOS) propagation.